Intangible Assets and Business Competitiveness: The Role of Intellectual Capital in Strategic Growth - Shukla, Shilpa (Journal of Global Economy, Business and Finance, 2025)
The Impact of Staff Training and Skills Development on Business Performance and Competitiveness" highlights the critical importance of intangible capital in the context of ever - changing economic challenges. Intangible capital encompasses assets such as staff knowledge, brand reputation and innovation. By investing in intangible capital, companies can gain significant competitive advantages, enhancing their agility, creativity and responsiveness to market changes. This results in an overall improvement in business performance. This work highlights how a strategic approach to the development of soft skills can stimulate economic growth while fostering a culture of learning and innovation, thus contributing positively and sustainably to their economic and social environment.